Analysis of Teacher Candidates' Attitudes Towards the School Experience Course - Kürşad Dönmez; Serdar Kocaekşi; Murat Kangalgil; Fatih Özgül (Pamukkale University, 2022)
The study aimed to determine the attitudes of the preservice teachers who have taken the school experience course. The participants consist of 3rd and 4th-grade students who studied at the Faculty of Education and Faculty of Sport Sciences during the 2017-2018 academic year at Sivas Cumhuriyet University. A total of 303 (60.6%) female and 197 (39.4%) male preservice teachers participated in the study. "Attitude Scale Towards School Experience Courses" developed by Kılınç and Salman (2007) was used for data collection. Descriptive statistics and One Way Analysis of Variance (ANOVA) tests were used to analyze the data. According to the findings, the total scores of the preservice teachers' attitudes towards the school experience scale were high, and the preservice teachers reported positive attitudes towards the school experience course. As a result, preservice teachers showed a positive attitude towards the school experience course, and the learning outcomes of the school experience course have been reached. In line with the findings obtained as a result of the study, suggestions were made to teachers and researchers.